Effects of fermented diet on reproductive performance and fecal microbiota for late-gestation sows - Sheng, Hai; Liu, Chaoqi; Li, Zhentian; Wang, Ping; Wang, Lijun; Jin, Sanjun; Li, Xinxin; Yuan, Lin; Chang, Juan; Yin, Qingqiang; Zhu, Qun; Lu, Fushan (Frontiers in Nutrition, 2025)
The late-gestation period is a key stage in the reproductive cycle of sows, which is related to the health of sows and the fetal development. In order to increase sow reproduction in late gestation, the fermented diet was produced and applied in this study. A total of 24 sows in the third pregnancy were divided into four groups on the 80th day gestation, 6 sows in each group. Group A was a basal diet served as the control group; groups B, C and D were added with 5, 10 and 15% fermented diet, respectively. The experiment was 35 days (from the 80th day gestation until parturition). The results showed that the sows in group D exhibited the best reproductive performance. Compared to group A, litter weight in group D was increased by 24.91% (P< 0.05). Additionally, crude protein digestibility in groups B, C, and D was significantly higher than that in group A (P< 0.05). Serum levels of TC, TG, IL-6, TNF-α, ROS and MDA in group D were significantly decreased, while serum levels of TP, ALB, GLB, IL-10, IgA, IgG and GSH-Px were significantly increased, compared with group A (P < 0.05). 16S rRNA analysis indicated that the relative abundances of Bacteroidota, Turicibacter and norank_f__Muribaculaceae in group D were significantly increased, while the relative abundances of Proteobacteria, Escherichia-Shigella and Aerococcus were significantly decreased, compared with group A (P < 0.05). The abundances of other genera between groups A and D were insignificantly different (P > 0.05). In conclusion, the fermented diet addition in the basal diet of late-gestation sows could adjust the balance of gastrointestinal microbiota as well as enhance protein digestibility, anti-oxidative capacity and immunity for improving their reproductive performance.